Transoral endoscopic thyroidectomy by vestibular approach (TOETVA) : initial experience in Brazil (2018)
ABSTRACT: Objective: to present the initial experience in Brazil with transoral endoscopic thyroidectomy by vestibular approach (TOETVA). Methods: prospective study of patients undergoing TOETVA in the Department of Head and Neck Surgery of Hospital Regional do Oeste, Chapecó, Santa Catarina. Patients between 18 and 65 years of age, ASA I and II, with maximum glandular volume of 35cm3 and nodules up to 4cm were candidates for the study. Data of the patients, nodules, surgical time, complications, and length of hospital stay were recorded. Results: nine patients were operated between May 2017 and April 2018. All were women, aged 33-64 years. The size of the nodule ranged from 1cm to 4cm. Two patients had malignant neoplasia and total thyroidectomy was performed in eight cases. Seven patients were hospitalized for only one day. One patient had a minor complication on skin, but there were no lesions of the laryngeal recurrent nerves or definitive hypoparathyroidism. Conclusion: TOETVA is a safe technique for well-selected patients, with favorable conditions and special concern for aesthetic results.